2021
DOI: 10.1038/s41598-021-02236-9
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes and predation marks shed new light on ammonoid habitat depth preferences

Abstract: Ammonoids are extinct cephalopods with external shells which predominated in many late Paleozoic and Mesozoic marine ecosystems. Stable isotope data from ammonoid shells constitute primary tools for understanding their palaeohabitats. However, in most sedimentary successions globally the aragonitic shells of ammonoids are dissolved during fossilisation process and therefore not available for geochemical studies. We overcome this taphonomic bias by analysing the better preservable calcitic elements of the ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…See the 'Supplementary Information' in Machalski et al (2021) for a full description of the section and its fossil assemblages. Macrofossil assemblages at Chełm are rather poor in diversity and number of specimens, being dominated by small-to mediumsized bivalves, echinoids and ammonites (Dubicka & Peryt, 2011;Machalski et al, 2021). In terms of macrofossil biostratigraphy (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…See the 'Supplementary Information' in Machalski et al (2021) for a full description of the section and its fossil assemblages. Macrofossil assemblages at Chełm are rather poor in diversity and number of specimens, being dominated by small-to mediumsized bivalves, echinoids and ammonites (Dubicka & Peryt, 2011;Machalski et al, 2021). In terms of macrofossil biostratigraphy (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Dubicka & Peryt (2012) assigned the Chełm section to their local foraminiferal zones VIII (lowest part), IX (bulk of section) and X (top of section). Based on planktic foraminiferal spectra (Dubicka & Peryt, 2011 and the shape of the carbon isotope curve, Machalski et al (2021;Supplementary Information) concluded that the Chełm section corresponded to the interval between c. 180 and 115 m in the Stevns-1 reference borehole in Denmark, as described by Thibault et al (2012) and Surlyk et al (2013). This interval represents the Hvidskud Member of the Møns Klint Formation, which comprises the topmost part of the UC19, entire UC20a and lower part of the UC20b-c nannofossil zones, and three magnetostratigraphic zones, namely 31n, 30r and 30n.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears like most if not all ammonoid hatchlings were planktic (Kulicki 1974(Kulicki , 1979(Kulicki , 1996Drushchits et al 1977;Tanabe et al 1980Tanabe et al , 2001Tanabe et al , 2003Landman 1985;Tanabe and Ohtsuka 1985;Shigeta 1993;Landman et al 1996;Westermann 1996;Rouget and Neige 2001;Mapes and Nützel 2009;Tajika and Wani 2011;De Baets et al 2012, 2015Ritterbush et al 2014;Lemanis et al 2015). However, several Jurassic and Cretaceous ammonoids have been interpreted as having been demersal during their post-embryonic or adult stages based on oxygen isotopic examinations (Moriya et al 2003;Lécuyer and Bucher 2006;Lukeneder et al 2010;Moriya 2015a, b;Sessa et al 2015;Linzmeier et al 2018;Hoffmann et al 2019;Machalski et al 2021). Among those lineages, we focused on the family Tetragonitidae (Lytoceratoidea) for this study.…”
Section: Introductionmentioning
confidence: 99%